2011
DOI: 10.1136/ard.2010.141523
|View full text |Cite
|
Sign up to set email alerts
|

Remission is the goal for cardiovascular risk management in patients with rheumatoid arthritis: a cross-sectional comparative study

Abstract: Patients with active RA, but not those in remission, had significantly increased levels of CVD risk markers. These results link inflammatory activity to markers of CVD risk in patients with RA and may indirectly support the notion that remission in RA confers diminished cardiovascular morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 51 publications
2
68
1
4
Order By: Relevance
“…Others have shown similar cardiovascular disease risk stratifications based on rheumatoid arthritis disease activity 174. In the RORA-AS trial, lower rheumatoid arthritis disease activity was associated with greater carotid plaque regression 164…”
Section: Management and Prevention Of Cardiovascular Disease In Rheummentioning
confidence: 92%
“…Others have shown similar cardiovascular disease risk stratifications based on rheumatoid arthritis disease activity 174. In the RORA-AS trial, lower rheumatoid arthritis disease activity was associated with greater carotid plaque regression 164…”
Section: Management and Prevention Of Cardiovascular Disease In Rheummentioning
confidence: 92%
“…Some authors consider it to be a sensitive noninvasive predictor of subclinical CVD in these patients and a predictor of all-cause mortality independent of traditional CV risk factors [61]. There is evidence that NT-proBNP is increased in RA patients and it is associated with inflammatory markers [35,61]. However, some studies did not demonstrate relationship between NTproBNP levels and LV function in RA patients.…”
Section: Rheumatoid Arthritis and Heart Failurementioning
confidence: 96%
“…Dyslipidemia, commonly observed in patients with active RA, appears to be present very early in the disease development. Majority of studies detected lower total cholesterol (TC) levels as well as lower levels of highdensity lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) in RA patients as compared with non-RA subjects, although overall incidence of dyslipidemia was higher in RA [27,[33][34][35]. Only some studies demonstrated typical atherogenic lipid profile in these patients [36,37].…”
Section: Dyslipidemiamentioning
confidence: 97%
“…In addition, certain drugs may have additional benefits (and some harm) with regard to cardiovascular safety in RA. Provan et al [22 ] found that patients with active RA had significantly increased brachial and central systolic pressure compared to RA patients in remission and healthy controls [22 ]. In contrast, patients in remission did not differ from controls on most of the vascular function measures assessed but did have reduced aortic pulse wave velocity (PWV) when compared to healthy controls.…”
Section: Conventional Disease Modifying Antirheumatic Drugs and Cardimentioning
confidence: 96%